The nature of teacher feedback in second language (L2) writing classrooms: A study on some private universities in Bangladesh - Karim, Md Ziaul; Ivy, Taslima Irine (Journal of the Bangladesh Association of Young Researchers, 2011)
The core task of second language (L2) writing teachers is to help students become efficient writers by building up student confidence and providing effective strategies to improve student writing. Teacher feedback given during various stages of process writing can play a vital role in this respect. This paper tried to find out the prevalent forms and nature of teacher feedback in L2 writing classrooms of some private Universities (e.g. dominant forms of feedback, the effect of feedback, amount of importance attached to feedback sessions, attitude towards students in the process & teacher training on feedback). At the same time it also looked into the effect of feedback on students (whether students view feedback as important, what kinds of feedback students prefer, what they expect from the teacher & whether they feel positive about feedback). Based on these findings some suggestions based on recent literature were added to help improve feedback methods according to one's context. Key words: Feedback to L2 writing; Feedback in ESL/EFL classroom; Feedback nature and type in Bangladesh. DOI: 10.3329/jbayr.v1i1.6837 Journal of Bangladesh Association of Young Researchers Vol.1(1) 2011 pp.31-48